Meditatio Septuaginta: Torah recitation as a spiritual discipline - Boyd-Taylor, Cameron (HTS teologiese studies, 2021)
There is evidence that the practice of meditative reading was cultivated by Hellenistic Jews as a discipline analogous to the spiritual exercises of the philosophical schools. The present study traces (1) the Deuteronomic antecedents of this practice, (2) its reconfiguration in the Torah Psalms, and (3) finally its expression in Greco-Jewish translation, with special reference to the Greek Psalter. Taking its cue from the work of Pierre Hadot, it situates this development within the larger matrix of Hellenistic philosophical discourse. The philological focus of the study is the use of the Hebrew verb I הגה Qal in contexts where Torah study is thematic and its rendering by μελετάω in the Septuagint. To frame the lexical analysis, it draws on the slot-filler model pioneered by Charles Fillmore.Contribution: This article situates a key Greco-Jewish translation with reference to both its Deuteronomic antecedents and to practices cultivated within the philosophical schools of the Hellenistic period. The analysis demonstrates the relevance of Frame Semantics to philological investigation.